Analisis Faktor-Faktor Penyebab Rendahnya Tingkat Melanjutkan Pendidikan Ke Perguruan Tinggi (Studi Kasus Di Desa Kalijaga Timur Lombok Timur) - Diana; Sumardi, Lalu; Sawaludin, Sawaludin (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study was motivated by the low rate of children continuing their education to college in Kalijaga Timur Village, East Lombok Regency. This condition is interesting to study because there are still many high school graduates who choose not to continue their higher education, even though they have the desire and potential to do so. The focus of this study is to analyze the factors causing the low rate of continuing education to college and to describe the role of parents in supporting the continuity of their children's education. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews and documentation involving the village head, parents of students, and high school graduates as informants. The results of the study show that the low continuity of children's education to college is caused by three main factors, namely economic factors, social and cultural environmental factors, and the desire to earn money. The role of parents in the continuity of their children's education is reflected through emotional support in the form of motivation and encouragement, as well as informational support regarding educational opportunities and scholarships. The results of this study confirm that the continuity of children's education is influenced by the socio-economic conditions of the family, the mindset of the community, and the active role of parents in supporting their children's education. Keywords: Educational Continuity, Economic Factors, Parental Support